Complicated thromboembolic prophylaxis in the treatment of septic gonitis – case report - Adrian Brychcy; Wojciech J. Marczyński; Stanisław Rak (Pediatria i Medycyna Rodzinna, 2015)
In this paper the case of a patient subjected to orthopaedic treatment with a history of a number of internal comorbidities, cardiac ones in particular, has been reported. Cardiac comorbidities were related to the implantation of a VVI pacemaker. The patient was chronically administered acenocoumarol with a standard INR control. He developed infectious arthritis of the left knee joint. The  condition was the indication for surgery. The  surgical treatment was performed with the implementation of antithrombotic prophylaxis using low-molecular-weight heparin at a dose as prescribed by a cardiologist. The prescribed dosage of nadroparin – 100 mg – was higher than indicated in both Polish and international regimen standards. Higher dose was also maintained in next days that followed the surgery. Intra-articular haematoma occurred as a post-surgery complication, hence the revision of the knee joint was performed. The haematoma was diagnosed intraoperatively, then removed and pulsed lavage was performed. Garamycin sponge was applied to treat the inflammation. A targeted antibiotic therapy was continued. Surgical site drainage was performed for one day without the use of negative pressure. Thromboembolic prophylaxis was implemented in accordance with the applicable dosage regimen in Poland. In view of a vast majority of thrombosis risk factors, prolonged prophylaxis with heparin and return to acenocoumarol were indicated once the surgical would had healed. As a result, other early and late postoperative complications were avoided.